The male reproductive system and endurance exercise - Hackney, A. C. (Medicine & Science in Sports & Exercise, 1996)
During the last decade extensive research on the role of exercise upon the human reproductive system has been conducted. Primarily these investigations have focused on female subjects, but an increasing number of studies have examined male related issues. Evidence now suggests that men who participate in chronic endurance training display mild degrees of reproductive system abnormalities. The major abnormalities noted thus far are reduced resting levels of testosterone, altered pituitary release of luteinizing hormone and prolactin, and altered sperm characteristics. The purpose of this article is to briefly review the research literature on this topic and address select aspects of the impact of exercise upon the male reproductive system. The principal topics addressed in this article are acute and chronic exercise effects, consequences of hormonal changes associated with endurance training, and potential mechanisms for the reproductive system changes detected.